Carbon Monoxide and the Brain: Time to Rethink the Dogma - Hanafy, Khalid A. (2013)
Carbon Monoxide (CO), long thought to be a simple environmental pollutant is now known to have a critical role in cellular functions ranging from vasodilation to circadian rhythms. In this review, we will begin with a discussion of the enzyme responsible for CO production: heme oxygenase. Because this review will focus on the effects of CO in the brain, we will transition to CO toxicology and determine if this simple diatomic gas has really earned its nefarious reputation. An in depth analysis of the roles for CO in circadian rhythms and as a gasotransmitter will be provided in the neurological functional role section, followed by its vascular effects derived mainly from interactions with soluble guanylyl cyclase. We will then describe the evidence for CO’s protective roles through the MAPK pathway, and finally touch upon the potential therapeutic roles for CO in neurological diseases including ischemic stroke, multiple sclerosis, and neuropathic pain.